Small bowel obstruction exacerbated by barium sulfate administration - Whitney L. Reid, DO; Jesse L. Cox, MD, PhD; Karen L. Pennington; Philip McCarthy, DO; Vishal M. Kothari, MD, FACS; Samuel M. Cohen, MD, PhD (Elsevier, 2019)
Small bowel obstruction (SBO) is a commonly encountered medical condition, typically a result of extrinsic causes, including post-operative adhesions. Less frequently, intrinsic and intraluminal factors may cause obstruction. Barium sulfate is a widely used contrast agent for radiography of suspected SBO, though it is rarely encountered in histologic sections and is an uncommon cause of SBO. Here, we present a case of a patient with several risk factors for SBO who received routine diagnostic imaging. Surgical resection revealed gross adhesions and histology showed intraluminal foreign material, determined to be barium sulfate by scanning electron microscopy with energy dispersive x-ray spectroscopy. Keywords: Small bowel obstruction, Barium sulfate, Dysmotility